POLITICAL STRUGGLE OVER THE IMMIGRATION REFORM DURING G.W.BUSH PRESIDENCY - A. A. Filippenko (Vestnik MGIMO-Universiteta)
By the beginning of the XXI century, the US had about 12 million illegal aliens and the immigration reform was evidently much needed. The Immigration Act of 1990 was significantly outdated and required revision. Additional regulations that passed in the 1990-s had to be systematized. The White House and the president George W. Bush inclined to the comprehensive immigration reform that would include an amnesty for the certain part of the illegal aliens. Some lawmakers were ready to strike a deal, but than happened the 9/11 tragedy. Immigration reform was shelved and turned into a matter of national security. Immigration reform bills were taken into consideration only in conjunction with boarder security bills. Edward Kennedy was very much aware of the issue's complexity and the need for reform; he did all he could to reach a compromise with his fellow Republicans. John McCain became his closest ally in the reform. Democrats made considerable concessions, while moderate Republicans were willing to meet them halfway, but the conservatives would not let the Congress adopt a new legislation, calling any attempt at comprehensive immigration reform an amnesty for the criminals. During the 107-110 Congresses the immigration reform was thoroughly worked through from both sides, but the proposed bills rarely got to the floor and never passed both Houses. Even though the time has passed, suggestions offered and deals reached during the Bush presidency did not lose the edge and any new immigration legislation is going be based on the 2002-2008 bills.